2015
DOI: 10.1021/acs.joc.5b01236
|View full text |Cite
|
Sign up to set email alerts
|

Resolution and Determination of the Absolute Configuration of a Twisted Bis-Lactam Analogue of Tröger’s Base: A Comparative Spectroscopic and Computational Study

Abstract: The first reported twisted bis-lactam, a racemic Tröger's base (TB) analogue (2), was resolved into its enantiomers on a chiral stationary phase HPLC column. The absolute configuration of (+)-2 was determined to be (R,R)-2 by comparing experimental and calculated vibrational circular dichroism (VCD) and electronic circular dichroism (ECD) spectra. The absolute configuration of (-)-2 was determined by comparing experimental and calculated electronic circular dichroism (ECD) spectra. The corresponding theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Benzofused 1-azabicyclo[3.3.1]­nonan-2-one derivative ( 2 ) has been used by us to demonstrate N-alkylation and the subsequent σ N–C bond cleavage of bridged lactams . Methyl-truncated Tröger’s base twisted amides 3 and 4 are analogues of the amides reported by Wärnmark and Cvengroš, respectively. , Amides 5 and 6 are Tröger’s base analogous of 3 and 4 lacking benzene rings, while twisted urea 7 was selected on the basis of the potential bridgehead oxidation in the course of synthesis of 3 . Note that related bridgehead iminium ions are well-known .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Benzofused 1-azabicyclo[3.3.1]­nonan-2-one derivative ( 2 ) has been used by us to demonstrate N-alkylation and the subsequent σ N–C bond cleavage of bridged lactams . Methyl-truncated Tröger’s base twisted amides 3 and 4 are analogues of the amides reported by Wärnmark and Cvengroš, respectively. , Amides 5 and 6 are Tröger’s base analogous of 3 and 4 lacking benzene rings, while twisted urea 7 was selected on the basis of the potential bridgehead oxidation in the course of synthesis of 3 . Note that related bridgehead iminium ions are well-known .…”
Section: Resultsmentioning
confidence: 99%
“…Stimulated by our interest in the properties of nonplanar cyclic and acyclic amides, we were attracted by the recently reported examples of Tröger’s base twisted amides , as models for a substantial twist of the amide bond. In 2012, Wärnmark and co-workers demonstrated that direct oxidation of the venerable Tröger’s base scaffold can be used to afford a twisted bis-amide with a remarkable twist of the amide bond (Figure B, τ = 41.0°, χ N = 57.9°, N–C­(O) = 1.430 Å, CO = 1.210 Å). In 2017, Cvengroš and co-workers reported the synthesis of an extended Tröger’s base twisted amide using one-step oxidation of the ethano-Tröger’s base (Figure B, τ = 29.8°, χ N = 45.5°, N–C­(O) = 1.401 Å, CO = 1.215 Å).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology elegantly exploits the high electrophilicity of the carbonyl group in twisted amides, providing direct access to stereochemically defined Tröger's base derivatives after hydrogenation. The authors showcased the utility of the thus‐obtained products in the synthesis of macrocyclic crown ether analogues of Tröger's base …”
Section: Twisted Amides: New Frontiersmentioning
confidence: 99%
“…The absolute configuration of the isolated TPA enantiomers was determined using ECD spectroscopy. The absolute configuration assignment is significant for understanding the stereoselective bioactivity (Rúnarsson et al, ), and the sign of the optical rotation is subject to error in the stereochemical assignment (Zhang et al, ). Therefore, ECD experiments were carried out to confirm the absolute configuration of the chiral TPA enantiomers.…”
Section: Resultsmentioning
confidence: 99%